Digital Literacy Assisted by Mobile Learning Based on Articulate Storyline in Learning to Understand Poetry - Kurniawati, Erika; Pairin, Udjang; Indarti, Titik; Efendi, Agik Nur; Prakoso, Yogo Arif (UNDIKMA, 2024)
The independent curriculum goes hand in hand with the rapid development of technology. Students must go alongside with various technologies. Digital literacy is not just about students being able to operate technology.This learning is applied to the material of understanding poetry in class X SMK. This research uses a descriptive qualitative approach with interview and observation models as data sources. The results show that android-based learning is in accordance with the needs of students. This research aims to provide an overview of how effective the application made by the author to be applied for education in school. The results show that mobile learning is a digital learning media which is in accordance with students’ needs.